Effects of COMT, DRD2, BDNF, and APOE Genotypic Variation on Treatment Efficacy and Cognitive Side Effects of Electroconvulsive Therapy. Issue 2 (June 2015) - Bousman, Chad A.; Katalinic, Natalie; Martin, Donel M.; Smith, Deidre J.; Ingram, Anna; Dowling, Nathan; Ng, Chee; Loo, Colleen K.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to explore the main and interaction effects of the COMT Val158Met, DRD2 C957T, BDNF Val66Met, and APOE polymorphisms on treatment efficacy and cognitive side effects of electroconvulsive therapy (ECT). Methods A total of 117 adult inpatients with a diagnosis of major depressive disorder recruited from 3 hospitals were administered the Montgomery-Äsberg Depression Rating Scale and a cognitive battery assessing global cognition, anterograde memory, executive function, speed and concentration, as well as retrograde memory at baseline and after ECT treatment. Results DRD2 C957T heterozygotes had 3.7 (95% confidence interval, 1.13–12.25; P = 0.032) greater odds of remission compared with CC homozygotes. Among the men, COMT Val/Val carriers had greater depressive symptom reduction compared with Met/Met carriers (Montgomery-Äsberg Depression Rating Scale percentage of reduction, 76% vs 35%; P = 0.020) but not among the women (P = 0.903) after ECT. For cognitive outcomes, an interaction effect on anterograde memory was observed between the DRD2 and BDNF polymorphisms (P = 0.016), in which carriers of the DRD2 TT and BDNF Val/Val genotypes had significantly less decline in anterograde performance than those that carried the TC and Met-allele (P = 0.001) or CC and Met-allele (P = 0.003) genotypes. However, no results withstood correction for multiple comparisons. Conclusions These observations provide preliminary evidence supporting an association between common functional genotypic variation and ECT efficacy as well as anterograde memory side effects after ECT. Validation of these findings is required before firm conclusions can be made and clinical utility can be assessed.